Energy Transfer from Ce3+ to Tb3+/Dy3+/Mn2+ in Ca9Ga(PO4)7 Phosphors: Synthesis, Structure and Tunable Multicolor Luminescent Properties. Issue 6 (28th February 2019) - Kang, Xiaojiao; Lü, Wei; Wang, Hongcheng; Ling, Dongxiong
Abstract: A series of Ca9 Ga(PO4 )7 :Ce 3+ /Tb 3+ /Dy 3+ /Mn 2+ phosphors with tunable color, in which Ce 3+ acts as the sensitizer, was synthesized. Energy transfer (ET) from Ce 3+ to Tb 3+ /Dy 3+ /Mn 2+ was investigated in detail. Tb 3+ /Dy 3+ /Mn 2+ single‐doped Ca9 Ga(PO4 )7 can exhibit green, yellow, and red emission, respectively. Incorporating Ce 3+ into a Tb 3+ /Dy 3+ /Mn 2+ single‐doped Ca9 Ga(PO4 )7 phosphor can remarkably promote the luminous efficiency of the Tb 3+ /Dy 3+ /Mn 2+ ions. This enhancement originates from an efficient ET from Ce 3+ to Tb 3+ /Dy 3+ /Mn 2+ . The ET was validated by luminescence spectra, decay dynamics, and schematic energy levels. Moreover, the intensity ratio of red emission of Mn 2+ to violet emission of Ce 3+ was analyzed based on energy‐transfer and lifetime measurements. In Ce 3+ ‐Tb 3+, Ce 3+ ‐Dy 3+, and Ce 3+ ‐Mn 2+ doped Ca9 Ga(PO4 )7, the emitting color changed from violet to green, yellow, and red, respectively, which indicates the potential use of this new tunable phosphor in UV light‐emitting diodes. Abstract : Energy transfer from Ce 3+ to Tb 3+ /Dy 3+ /Mn 2+ in Ca9 Ga(PO4 )7 is investigated as a function of the Ce 3+ /Tb 3+ /Dy 3+ /Mn 2+ concentration and based on the photoluminescence emission/excitation spectra and decay curves. Through dual energy transfer, the emitting colors can change to green, yellow, and red from the initial blue color. The results suggest that the material is suitable for UV‐white LEDs.